Factors associated with exclusive breastfeeding among mothers of infants aged 7–12 months in Bandar Lampung, Indonesia: A cross-sectional study - Renata Sheilawati; Rilyani Rilyani; Riska Wandini (School of Health Sciences Al-Ma'arif, 2026)
Background: Exclusive breastfeeding is an important maternal and child health practice, but coverage can vary markedly within the same administrative area. Pinang Jaya Public Health Center reported lower coverage than the Bandar Lampung city estimate, indicating a need for local evidence. Objective: To identify maternal and contextual factors associated with exclusive breastfeeding among mothers of infants aged 7–12 months in the working area of Pinang Jaya Public Health Center, Bandar Lampung, Indonesia. Methods: This cross-sectional study included all 40 eligible mothers registered in the health-center working area in November 2025. Knowledge was measured with 20 dichotomous items (score 0–20; good = 15–20). Attitude was measured with six five-point Likert items (score 6–30; positive = 23–30), and sociocultural support was measured with ten five-point Likert items (score 10–50; supportive = 38–50). Exclusive breastfeeding was determined using a structured infant-feeding history and checked against maternal and child health records when feeding information was available. Continuity-corrected Chi-square tests were used when expected cell counts were adequate; Fisher’s exact test was used for maternal age because the minimum expected count was 2.85. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for the odds of exclusive breastfeeding. Results: Exclusive breastfeeding was reported by 21 mothers (52.5%). Significant associations were observed for good knowledge (OR = 11.900; 95% CI = 2.674–52.959; p = 0.002), being unemployed compared with employed (OR = 16.800; 95% CI = 3.417–82.603; p < 0.001), high education (OR = 8.960; 95% CI = 2.140–37.522; p = 0.005), positive attitude (OR = 10.667; 95% CI = 2.308–49.306; p = 0.003), and supportive sociocultural conditions (OR = 10.667; 95% CI = 2.308–49.306; p = 0.003). Maternal age and parity were not significantly associated with exclusive breastfeeding. Conclusion: Knowledge, employment status, education, attitude, and sociocultural support were associated with exclusive breastfeeding in this small health-center population.